Design of the Robust Synchronous Generator Stator Voltage Regulator Based on the Interval Plant Model - Stojić, Đorđe M.; Milinković, Milan; Veinović, Slavko; Joksimović, Dušan; Milojčić, Nemanja; Klasnić, Ilija; Arnautović, Dušan (Proceedings, Electrical engineering institute "Nikola Tesla", 2013)
In this paper, a novel method for the stator voltage regulator of a synchronous generator based on the interval plant mode is presented. Namely, it is shown in the literature that, in order to design a controller for the first-order compensator, the limited number of interval plants needs to be examined. Consequently, the intervals of the plant model parameter variations used to calculate the four extreme interval plants required for the sequential PI controller design are determined. The controller is designed using frequency-domain-based techniques, while its robust performance is examined using simulation tests.